Religious Guidance for Foster Parents in Building Self-Confidence for Young Women in Orphanages - Khairani, Ulfa; Zainun (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2024)
This research is motivated by the lack of self-confidence possessed by young women in orphanages because every teenager must have self-confidence in developing their personality so that they can become teenagers who know their life goals. This research aims to determine the religious guidance methods applied by foster parents. The research method used is qualitative research. Data collection techniques use observation, interviews and documentation. The data analysis used is data reduction, data presentation and concluding. The research results reveal that teenagers given religious guidance through lectures in the form of advice and motivation can become more confident in their abilities and belief in themselves. Teenagers in orphanages are more confident, open to their environment, able to accept themselves, take responsibility for their lives and develop their abilities. Apart from that, the implementation of guidance that has been carried out at the orphanage helps teenagers find courage for themselves and helps raise awareness to develop their abilities and potential optimally. For this reason, teenagers have provisions that can help them in the future. The novelty of this research focuses on research objects centred on teenagers, who need self-confidence so they can have good social relationships in their surrounding environment.